Perovskite-perovskite heterogeneous double-layer thin film and application thereof
By introducing functional additives into the perovskite precursor solution by a one-step solution method, the spontaneous step-by-step crystallization of perovskite-perovskite heterobilayer film is solved, and the problems of many heterojunction interfaces and complex preparation processes in the prior art are solved, and the preparation of high-quality films and high-performance optoelectronic devices are realized.
Patent Information
- Application Number
- CN202311251494.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-26
- Publication Date
- 2025-03-28
AI Technical Summary
The perovskite-perovskite heterojunctions in existing perovskite optoelectronic devices are usually gradient heterojunctions, with a large number of heterojunction interfaces, which affect the efficient transmission of carriers. In addition, existing technologies have limitations in material composition, heterojunction size, processing technology, etc., making it difficult to prepare high-performance optoelectronic devices on a large scale.
Through a one-step solution method, functional additives are used to introduce into the mixed-dimensional perovskite precursor solution, the spontaneous step-by-step crystallization of three-dimensional and low-dimensional perovskites is achieved, and the interface between perovskites in different dimensions is reduced, and a high-quality perovskite-perovskite heterobilayer film with a single clear heterojunction interface is obtained.
It realizes a large area controllable fabrication of high-quality perovskite-perovskite heterobilayer film, improves the crystallization quality and fluorescence quantum efficiency of the film, and is suitable for hole-free transport layer optoelectronic devices with simplified structure, showing excellent photoelectric performance.
Smart Images

Figure CN119707312A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of optoelectronic devices, and more specifically, relates to a perovskite-perovskite heterogeneous double-layer film and its application. Background Art
[0002] In recent years, perovskite-perovskite heterojunctions have shown great application potential in solar cells, light-emitting diodes, photodetectors and other fields due to their excellent optoelectronic properties (Nature 2022, 603, 73). However, the perovskite-perovskite heterojunctions in perovskite optoelectronic devices currently prepared by the solution method are usually gradient heterojunctions formed by self-assembly of perovskites of different dimensions (Nat. Photonics 2016, 10, 699), which have a large number of heterojunction interfaces, which easily affect the efficient transmission of carriers and are not conducive to the realization of high-performance devices. On the other hand, the reported perovskite-perovskite heterojunctions with a single heterojunction interface generally include the following four types: 1) Bulk heterojunction single crystals formed by utilizing the difference in crystallization rates of perovskites of different dimensions in hydrohalic acid solutions (Adv. Optical Mater. 2020, 8, 2000311); 2) Micro-nano heterojunctions formed by random physical stacking of two pre-prepared perovskite nanocrystals (Nat. Mater. 2022, 21, 1042); 3) Lateral heterojunctions obtained by local halogen exchange of single halogen perovskite crystals or films (Nature 2020, 580, 614); 4) Heterojunction films obtained by extensive screening of orthogonal solvents and depositing the upper two-dimensional perovskite by a solution method without dissolving the lower three-dimensional perovskite (Science 2022, 377, 1425). Among the above four perovskite-perovskite heterojunctions with a single interface, the first three heterojunctions have certain limitations in material composition, heterojunction size, processing technology, etc., which makes them unfavorable for the preparation of large-area optoelectronic devices. Although the fourth heterojunction can be applied to optoelectronic devices, due to the limitations of orthogonal solvents, there are fewer selectable perovskites and solvents, which limits its scope of application.
[0003] In addition, the heterojunctions reported above are mainly based on lead-based perovskites, and the toxicity of lead is bound to affect the commercial development of perovskites. Among lead-free perovskites, tin-based perovskites have similar structures and properties to lead-based systems, and are one of the ideal alternative materials for lead-based perovskites. In addition, tin-lead mixed perovskites have broad application prospects in the fields of stacked solar cells. Therefore, it is necessary to develop an effective method for universally preparing high-quality tin-based, lead-based, and tin-lead mixed perovskite-perovskite heterogeneous double-layer films. Summary of the invention
[0004] The purpose of the present invention is to provide a perovskite-perovskite heterogeneous double-layer film and its application in view of the shortcomings of the existing perovskite crystallization control technology. The present invention can realize the spontaneous step-by-step crystallization of three-dimensional and low-dimensional perovskites through a one-step solution method to obtain a high-quality perovskite-perovskite heterogeneous double-layer film with a single clear heterojunction interface.
[0005] In order to achieve the above object, the present invention provides a perovskite-perovskite heterogeneous double-layer film, wherein the heterogeneous double-layer film is LX, AX, BX 2 The functional additives are dissolved in a polar solvent and then obtained by a one-step solution method, and there is a heterojunction interface between the upper and lower layers of the heterogeneous double-layer film; one layer of the heterogeneous double-layer film is ABX 3 The other layer is a low-dimensional perovskite layer.
[0006] A is CH 3 NH 3 + HC(NH 2 ) 2 + , C(NH 2 ) 3 + , Cs + , Rb + and K + At least one of;
[0007] The B is Sn 2+ and / or Pb 2+ ;
[0008] X is F - , Cl - Br - and I - At least one of .
[0009] According to the present invention, preferably, the ABX of the heterogeneous double-layer film 3 The upper and lower layers composed of the three-dimensional perovskite layer and the low-dimensional perovskite layer also have the structural characteristics of an epitaxial heterojunction.
[0010] According to the present invention, preferably, the low-dimensional perovskite is LX and BX 2 The formation of zero-dimensional perovskite, LX and BX 2 Formed one-dimensional perovskites, LX and BX 2 The formed two-dimensional perovskite and LX, AX, BX 2 At least one of the co-formed quasi-two-dimensional perovskites.
[0011] According to the present invention, preferably, the LX, AX, BX 2The molar ratio is (0.05-1):(0.8-1.5):1:(0.01-0.8).
[0012] According to the present invention, preferably, the LX, AX, BX 2 and functional additives in the LX, AX, BX 2 The total mass concentration of the solution formed by the functional additive and the polar solvent is 5-50wt%.
[0013] According to the present invention, preferably, the LX is an organic ammonium salt and / or an organic phosphine salt obtained by an acid-base reaction of an organic amine and / or an organic phosphine with a hydrohalic acid, and is a large-sized organic salt; preferably, the organic amine is an organic amine having a carbon number of not less than 3; preferably, the organic phosphine is an organic phosphine having a carbon number of not less than 3; preferably, the hydrohalic acid is at least one of hydrofluoric acid, hydrochloric acid, hydrobromic acid and hydroiodic acid.
[0014] According to the present invention, preferably, the polar solvent is at least one of formamide, acetamide, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, cyclopentane, tetramethylene sulfoxide, 1,3-dimethylpropylene urea, γ-butyrolactone, γ-valerolactone, N-alkylpyrrolidone, acetonitrile, ethylene carbonate, propylene carbonate, methylammonium formate, methylammonium acetate, butylammonium acetate, methylammonium propionate and methylammonium isobutyrate; preferably, the polar solvent is a mixture of N,N-dimethylformamide and dimethyl sulfoxide. In the present invention, the mixing ratio of N,N-dimethylformamide and dimethyl sulfoxide can be arbitrary.
[0015] According to the present invention, preferably, the functional additive includes additive M, and optionally includes additive N. In the present invention, as a preferred embodiment, when the functional additive includes additive M and additive N at the same time, the perovskite heterogeneous double-layer film of the present invention with the best crystal quality can be obtained.
[0016] The additive M is the key to realize the perovskite heterogeneous double-layer film and can interact with LX. According to the present invention, preferably, the additive M is SnF 2 、SnF 4 , PbF 2 、ZnF 2 , MnF 2 ,CuF 2 , CdF 2 , FeF 2 , FeF 3 、NiF 2 , AlF 3 , CaF 2 MgF 2 , SrF 2At least one of AgF, tri(4-fluorophenyl)phosphine, tri(4-fluorophenyl)phosphine oxide and crown ether. Preferably, the additive M is SnF 2 .
[0017] The additive N is the key to improving the crystallization quality of the double-layer film and can be used together with LX, AX, BX 2 , the additive M interacts with each other. According to the present invention, preferably, the additive N is at least one of an amino acid additive, a vitamin additive, a quaternary ammonium salt additive and a quaternary phosphonium salt additive. Preferably, the additive N is at least one of alanine, valine, leucine, isoleucine, methionine, phenylalanine, tryptophan, tyrosine, asparagine, cysteine, glutamine, serine, threonine, aspartic acid, glutamic acid, arginine, histidine, lysine, glycine, 5-aminovaleric acid and proline. More preferably, the additive N is at least one of tryptophan, glycine, glutamic acid and 5-aminovaleric acid.
[0018] According to the present invention, preferably, the one-step solution method comprises: 2 , a solution formed by a functional additive and a polar solvent is coated on a substrate to obtain the heterogeneous double-layer film. More preferably, the one-step solution method comprises: 2 , a solution formed by functional additives and polar solvents and tin powder are stirred overnight, the tin powder is filtered off, and the filtrate is coated on the substrate to obtain the heterogeneous double-layer film. The function of the tin powder is to prevent the LX, AX, BX 2 , the solution formed by the functional additive and the polar solvent is oxidized.
[0019] According to the present invention, preferably, the substrate is at least one of an organic small molecule, an organic polymer, paper, leather, a metal, an inorganic compound, glass and a ceramic, preferably indium tin oxide (ITO), fluorine-doped tin oxide (FTO), lithium fluoride, tin oxide, zinc oxide, nickel oxide, poly (9-vinyl carbazole) (PVK), polyethylene dioxythiophene-polystyrene sulfonate (PEDOT:PSS), poly [bis (4-phenyl) (2,4,6-trimethylphenyl) amine] (PTAA), poly (N, N'-bis-4-butylphenyl-N, N'-biphenyl) benzidine (Poly- At least one of TPD), N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine (NPB), 1,3,5-tri(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi), 1,3,5-tri(3-pyridyl-3-phenyl)benzene (TmPyPB), 4,6-bis(3,5-di(3-pyridyl)phenyl)-2-methylpyrimidine (B3PYMPM) and poly[(9,9-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine)] (TFB).
[0020] According to the present invention, preferably, the one-step solution method is at least one of a one-step spin coating method, a one-step blade coating method and a one-step spray coating method.
[0021] In the present invention, as an optional solution, the one-step spin coating method includes an anti-solvent-assisted one-step spin coating method, and the anti-solvent is at least one of chlorobenzene, toluene, ethyl ether, anisole, ethyl acetate and dichloromethane.
[0022] According to the present invention, preferably, the operating conditions of the one-step spin coating method include: an ambient temperature of 5-45°C, preferably 20-40°C; a spin coating speed of 2000-10000rpm, preferably 5000-10000rpm; an annealing temperature after spin coating of 40-100°C, preferably 50-80°C; and an annealing time of 5-30min, preferably 10-15min.
[0023] Another aspect of the present invention provides the use of the perovskite-perovskite heterogeneous double-layer film in preparing an active layer of a photoelectric device.
[0024] According to the present invention, preferably, the optoelectronic device includes, in addition to the active layer, a substrate, an anode, an electron transport layer and a cathode, and optionally includes a hole transport layer. In the present invention, the hole transport layer can be omitted, and then an optoelectronic device without a hole transport layer is prepared.
[0025] In the present invention, as a preferred embodiment, the method for preparing the optoelectronic device comprises:
[0026] a) using detergent, acetone and ethanol to ultrasonically clean the transparent conductive glass, drying it with nitrogen after treatment, and then transferring the transparent conductive glass to an oxygen plasma cleaning machine to perform oxygen plasma cleaning under vacuum conditions;
[0027] b) depositing the perovskite-perovskite heterogeneous double-layer film of the present invention on the surface of the transparent conductive glass by a solution method, and performing thermal annealing; optionally, first depositing a hole transport layer on the surface of the transparent conductive glass by a solution method, and performing thermal annealing; then depositing the perovskite-perovskite heterogeneous double-layer film of the present invention on the surface of the hole transport layer by a solution method, and performing thermal annealing;
[0028] c) using a thermal evaporation method to sequentially deposit an electron transport layer, a buffer layer and a metal electrode on the surface of the perovskite-perovskite heterogeneous double-layer film of the present invention.
[0029] According to the present invention, preferably, the optoelectronic device is at least one of a solar cell, a light emitting diode, a photodetector and a memristor.
[0030] The beneficial effects of the technical solution of the present invention are as follows:
[0031] The present invention introduces functional additives into the mixed-dimensional perovskite precursor solution and, through component regulation and process optimization, can achieve spontaneous step-by-step crystallization of three-dimensional and low-dimensional perovskites, thereby reducing the interface between perovskites of different dimensions. A high-quality perovskite-perovskite heterogeneous double-layer film with a single clear heterojunction interface can be obtained through a one-step solution method.
[0032] The functional additive of the present invention can simultaneously passivate film defects, thereby further improving the film crystal quality, crystal orientation, and fluorescence quantum efficiency, thereby obtaining a film with high fluorescence quantum efficiency and a high-performance optoelectronic device.
[0033] The present invention realizes the large-area, batch-controllable preparation of high-quality perovskite-perovskite heterogeneous double-layer thin films, and can be applied to simplified optoelectronic devices without hole transport layers, and exhibits excellent optoelectronic performance. It solves the problems of the prior art in the preparation of perovskite-perovskite heterogeneous double-layer thin films, such as uncontrollable heterojunction size, complex preparation process, and poor compatibility with device structures.
[0034] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] The above and other objects, features and advantages of the present invention will become more apparent through a more detailed description of exemplary embodiments of the present invention in conjunction with the accompanying drawings, wherein like reference numerals generally represent like components throughout the exemplary embodiments of the present invention.
[0036] Figure 1 A schematic diagram of a one-step solution method preparation process of a perovskite-perovskite heterogeneous double-layer film according to Example 1 of the present invention is shown.
[0037] Figure 2a The in-situ absorption spectrum of the film of Comparative Example 1 of the present invention during the spin coating process is shown. (Wherein, Figure 2a-1 is the contour map of the in-situ absorption spectrum, Figure 2a -2 is the in-situ absorption spectrum line graph; "Wavelength" indicates wavelength; "Spin-coating time" indicates spin-coating time; "Absorbance" indicates absorbance)
[0038] Figure 2b The in-situ fluorescence (PL) spectrum of the film of Comparative Example 1 of the present invention during the spin coating process is shown (wherein, Figure 2b-1 is the contour map of the in-situ PL spectrum, Figure 2b -2 is the in-situ PL spectrum line graph; “PL intensity (Counts)” is the in-situ fluorescence intensity (counts)).
[0039] Figure 2c The SnF of Example 1 of the present invention is shown. 2 In situ absorption spectra of single-additive tin-based perovskite luminescent heterogeneous bilayer films during spin coating.
[0040] Figure 2d The SnF of Example 1 of the present invention is shown. 2 In situ fluorescence (PL) spectra of single-additive tin-based perovskite luminescent heterogeneous bilayer films during spin coating.
[0041] Figure 2e The in-situ absorption spectrum of the thin film of Comparative Example 2 of the present invention during the spin coating process is shown.
[0042] Figure 2f The in-situ fluorescence (PL) spectrum of the thin film of Comparative Example 2 of the present invention during the spin coating process is shown.
[0043] Figure 2g The in-situ absorption spectrum of the thin film of Example 2 of the present invention during the spin coating process is shown.
[0044] Figure 2h The in-situ fluorescence (PL) spectrum of the thin film of Example 2 of the present invention during the spin coating process is shown.
[0045] FIG3a shows the in-situ absorption spectrum of the film of Comparative Example 1 of the present invention during the annealing process. (where “Annealing” is annealing)
[0046] FIG3b shows the in-situ fluorescence spectrum of the film of Comparative Example 1 of the present invention during the annealing process under front-side excitation. (“Normalized PL” means normalized fluorescence intensity; “front side” means front side)
[0047] FIG. 3 c shows the in-situ fluorescence spectrum of the film of Comparative Example 1 of the present invention during the annealing process when excited from the back side (“back side”).
[0048] FIG. 3 d shows the in-situ absorption spectrum of the thin film of Example 1 of the present invention during the annealing process.
[0049] FIG. 3 e shows the in-situ fluorescence spectrum of the film of Example 1 of the present invention during the annealing process under front excitation.
[0050] FIG. 3 f shows the in-situ fluorescence spectrum of the film of Example 1 of the present invention under reverse excitation during the annealing process.
[0051] FIG. 3g shows the in-situ absorption spectrum of the thin film of Comparative Example 2 of the present invention during the annealing process.
[0052] FIG. 3 h shows the in-situ fluorescence spectrum of the thin film of Comparative Example 2 of the present invention under front excitation during the annealing process.
[0053] FIG. 3i shows the in-situ fluorescence spectrum of the film of Comparative Example 2 of the present invention under reverse excitation during the annealing process.
[0054] FIG. 3j shows the in-situ absorption spectrum of the thin film of Example 2 of the present invention during the annealing process.
[0055] FIG. 3 k shows the in-situ fluorescence spectrum of the film of Example 2 of the present invention under front excitation during the annealing process.
[0056] FIG. 31 shows the in-situ fluorescence spectrum of the film of Example 2 of the present invention under reverse excitation during the annealing process.
[0057] Figure 4a The SEM image of the film of Comparative Example 1 of the present invention is shown ( Figure 4a-1 , 4a-2 is the surface; Figure 4a -3 is the cross section).
[0058] Figure 4b The SEM image of the film of Example 1 of the present invention is shown ( Figure 4b-1 , 4b-2 is the surface; Figure 4b -3 is the cross section).
[0059] Figure 4c The SEM image of the film of Comparative Example 2 of the present invention is shown ( Figure 4c-1 , 4c-2 is the surface; Figure 4c -3 is the cross section).
[0060] Figure 4d The SEM image of the film of Example 2 of the present invention is shown ( Figure 4d-1 , 4d-2, and 4d-3 are all surfaces).
[0061] FIG. 5 a shows the PLQE (photoluminescence quantum efficiency) data of the films of Example 1, Comparative Example 1 and Comparative Example 2 of the present invention, which are dependent on the excitation light intensity (where “Light intensity” is the excitation light intensity).
[0062] Figure 5b shows the JVR (current density-voltage-irradiance) curves ("Current density" current density; "Voltage" voltage; "Radiance" irradiance) of the LED devices prepared from the thin films of Example 1, Comparative Example 1 and Comparative Example 2 of the present invention.
[0063] FIG. 5 c shows the EQE (external quantum efficiency) curves of the LED devices prepared using the thin films of Example 1, Comparative Example 1, and Comparative Example 2 of the present invention.
[0064] Figure 6 A cross-sectional SEM image of an LED device prepared using the thin film of Example 2 of the present invention is shown.
[0065] FIG. 7 a shows a cross-sectional scanning transmission electron microscope (STEM) photograph of an LED device fabricated using the thin film of Example 2 of the present invention.
[0066] FIG7 b shows high-angle annular dark field imaging (HAADF) and X-ray energy spectrum element distribution (EDS mapping) of a cross section of an LED device prepared by the thin film of Example 2 of the present invention (wherein the left is HAADF and the right is EDS mapping; “Counts” indicates EDS intensity counts and “Distance” indicates relative distance).
[0067] FIG. 7c shows a GIWAXS (grazing incidence wide angle scattering) two-dimensional image of the film of Example 2 of the present invention (X-ray incident angle α is 0.3°) (where “q z (A -1 )” indicates the out-of-plane direction; “q r (A -1 )” indicates the in-plane direction; “Intensity” indicates the GIWAXS signal intensity).
[0068] FIG. 7d shows the q of the film of Example 2 of the present invention at different incident angles. zThe GIWAXS intensity curve, where the X-ray incident angle α is 0.1° and 0.3°, corresponds to the X-ray penetration depth of about 3-5nm and more than 100nm. (“2θ (degree)” is the angle between the incident X-ray and the diffraction line in ordinary XRD test)
[0069] FIG. 7e is a schematic diagram showing the out-of-plane structure of the film of Example 2 of the present invention.
[0070] FIG. 7 f shows a schematic diagram of the in-plane structure of the film of Example 2 of the present invention.
[0071] FIG. 7g shows a surface transmission electron microscope (STEM) photograph of the thin film of Example 2 of the present invention.
[0072] FIG. 7 h shows a selected area electron diffraction (SAED) photograph of random grains of the thin film of Example 2 of the present invention.
[0073] FIG. 7i shows a selected area electron diffraction (SAED) photograph of random grains of the thin film of Example 2 of the present invention.
[0074] Figure 8 The GIWAXS data analysis chart of the film of Example 2 of the present invention is shown.
[0075] Figure 9a The PEAI, HC (NH 2 ) 2 Chemical structure diagram of I (FAI) and Trp;
[0076] Figure 9b-9d The liquid nuclear magnetic resonance spectra of each chemical component of the film of Example 2 of the present invention are shown respectively. (“Intensity” means intensity, 1 H chemical shift" means 1 The chemical shift of H, 119 Sn chemical shift 119 Chemical shift of Sn).
[0077] Fig.10 A schematic diagram showing the comparison of the crystallization process of the thin film of Comparative Example 1 and Example 2 of the present invention. (“Stage I” is the beginning of the nucleation stage, “Stage II” is the end of the spin coating stage, “Stage III” is the end of the annealing stage, and “ITOglass” is ITO glass)
[0078] FIG. 11 a shows the PLQE (photoluminescence quantum efficiency) data of the film of Example 2 of the present invention, which is dependent on the excitation light intensity.
[0079] FIG. 11b shows a schematic diagram of the energy level structure of an LED device prepared by the thin film of Example 2 of the present invention. (“Energy” means energy)
[0080] FIG. 11 c shows the electroluminescence (EL) spectrum (“EL intensity”) of the LED device fabricated from the thin film of Example 2 of the present invention.
[0081] FIG. 11 d shows the JVR curve of the LED device prepared using the thin film according to Example 2 of the present invention.
[0082] FIG. 11e shows the EQE curve of the LED device prepared using the thin film according to Example 2 of the present invention.
[0083] FIG11f shows a peak EQE statistical diagram of an LED device prepared by the thin film of Example 2 of the present invention. (“Number of device” indicates the number of devices; “Peak EQE” indicates the peak EQE)
[0084] FIG. 12a shows a large-area LED (effective area 70 mm2) prepared by the film of Example 2 of the present invention. 2 )A physical picture of the device.
[0085] FIG. 12b shows a large-area LED (effective area 70 mm2) prepared by the film of Example 2 of the present invention. 2 ) JVR curve of the device.
[0086] FIG. 12c shows a large-area LED (effective area 70 mm2) prepared by the film of Example 2 of the present invention. 2 )EQE curve of the device.
[0087] FIG. 12d shows a large-area LED (effective area 70 mm2) prepared by the film of Example 2 of the present invention. 2 ) Peak EQE statistics of the device.
[0088] Fig.13a The surface SEM images of the films of Examples 3 and 4 of the present invention are shown ( Figure 13a-1 For Example 3; Fig.13a -2 is Example 4)
[0089] Fig.13b The cross-sectional SEM images of the films of Examples 3 and 4 of the present invention are shown ( Figure 13b-1 For Example 3; Fig.13b -2 is Example 4)
[0090] FIG. 13 c shows the X-ray diffraction (XRD) of the thin films of Examples 3 and 4 of the present invention.
[0091] FIG. 13 d shows the front-excited fluorescence spectra of the films of Examples 3 and 4 of the present invention.
[0092] FIG. 13 e shows the fluorescence spectra of the films of Examples 3 and 4 of the present invention under reverse excitation.
[0093] FIG. 13f shows the electroluminescence (EL) spectra of LED devices prepared using the thin films of Examples 3 and 4 of the present invention.
[0094] FIG. 13g shows the JVR curves of the LED devices prepared using the thin films of Examples 3 and 4 of the present invention.
[0095] FIG. 13h shows the EQE curves of LED devices prepared using the thin films of Examples 3 and 4 of the present invention.
[0096] Fig.14a The figure shows the contour map of the in-situ fluorescence spectrum of the thin film of Example 5 of the present invention under different anti-solvent dropping time conditions during the spin coating process. Figure 14a-1 18s; Fig.14a -2 for 30s)
[0097] Fig.14b The surface SEM photograph of the film of Example 5 of the present invention is shown. Figure 14b-1 18s; Fig.14b -2 for 30s)
[0098] Fig.14c The cross-sectional SEM image of the film of Example 5 of the present invention is shown. Figure 14c-1 18s; Fig.14c -2 for 30s)
[0099] Fig.14d The in-situ fluorescence (PL) spectra of the film of Example 5 of the present invention under front and back excitation are shown. Figure 14d-1 18s; Fig.14d -2 for 30s)
[0100] FIG. 14 e shows the electroluminescence (EL) spectrum of the LED device prepared using the thin film of Example 5 of the present invention.
[0101] FIG. 14 f shows the JVR curve of the LED device prepared using the thin film of Example 5 of the present invention.
[0102] FIG. 14g shows the EQE curve of the LED device prepared using the thin film of Example 5 of the present invention.
[0103] FIG. 15 a shows the surface morphology of the film according to Example 6 of the present invention.
[0104] FIG. 15 b shows the fluorescence spectra of the film of Example 6 of the present invention when excited from the front and back surfaces.
[0105] FIG. 15 c shows a schematic diagram of the energy level structure of the LED device according to Example 6 of the present invention.
[0106] FIG. 15 d shows the JVR curve of the LED device according to Example 6 of the present invention.
[0107] FIG. 15 e shows the EQE curve of the LED device according to Example 6 of the present invention.
[0108] FIG. 15 f shows a peak EQE statistical diagram of the LED device according to Example 6 of the present invention.
[0109] Fig.16 a shows a surface SEM photograph of the thin film of Example 7 of the present invention.
[0110] Fig.16 b shows the photovoltaic characteristic curve of the solar cell according to Example 7 of the present invention.
[0111] Fig.17 The current density-voltage curve of the detector in Example 8 of the present invention in the light and dark states is shown. (“dark” is dark, “light” is bright)
[0112] Fig.18a The in-situ fluorescence spectrum of the thin film of Comparative Example 3 of the present invention during the spin coating process is shown. Figure 18a-1 is the contour map of in situ fluorescence spectrum. Fig.18a -2 is the in situ fluorescence spectrum line graph)
[0113] Fig.18b The in-situ fluorescence spectrum of the thin film of Example 9 of the present invention during the spin coating process is shown.
[0114] Fig.19a The in-situ fluorescence spectrum of the thin film of Comparative Example 4 of the present invention during the spin coating process is shown.
[0115] Fig.19b The in-situ fluorescence spectrum of the thin film of Example 10 of the present invention during the spin coating process is shown.
[0116] FIG. 20 a shows the JVR curve of the LED device prepared using the thin film of Comparative Example 5 of the present invention.
[0117] FIG. 20 b shows the EQE curve of the LED device prepared using the thin film of Comparative Example 5 of the present invention.
[0118] FIG. 21 a shows the JVR curve of the LED device prepared using the thin film of Comparative Example 6 of the present invention.
[0119] FIG. 21 b shows the EQE curve of the LED device prepared using the thin film of Comparative Example 6 of the present invention. DETAILED DESCRIPTION
[0120] The preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described below, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to make the present invention more thorough and complete, and to fully convey the scope of the present invention to those skilled in the art.
[0121] Example 1
[0122] This embodiment provides a perovskite-perovskite heterogeneous double-layer film, wherein the heterogeneous double-layer film is obtained by a one-step solution method, and a heterojunction interface exists between the upper and lower layers of the heterogeneous double-layer film. The specific preparation method includes:
[0123] PEAI (2-phenylethylamine hydroiodide), HC (NH 2 ) 2 I (formamidine hydroiodide), CsI, SnI 2 、SnF 2 According to the molar ratio of 0.3:0.9:0.1:1:0.2, it was dissolved in a mixed solvent of DMF (N,N-dimethylformamide) and DMSO (dimethyl sulfoxide) with a volume ratio of 1:4 to prepare a solution with a mass fraction of 14%, and then tin powder (3 mg mL -1 ) in the presence of 20% tin and stirred overnight (the function of the tin powder is to prevent the solution from being oxidized). Then, a 0.2 μm polytetrafluoroethylene (PTFE) filter was used to filter out the tin powder in the solution, and then a one-step spin coating method (8000 rpm, 60 s, ambient temperature of 30° C.) was used. Figure 1 As shown in FIG. 1 , the solution from which the tin powder is filtered out (i.e., the perovskite precursor solution) is deposited on a transparent conductive glass ITO substrate and annealed at 60° C. for 15 min to obtain a SnF 2 Single-additive tin-based perovskite luminescent heterogeneous bilayer films.
[0124] This embodiment also provides a photoelectric device, using the SnF 2 The single additive tin-based perovskite luminescent heterogeneous double-layer film is used as the active layer of the optoelectronic device; the preparation method of the optoelectronic device also includes:
[0125] The electron transport layer 1,3,5-tri(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi) and the electrode LiF / Al were deposited by thermal evaporation to obtain a perovskite light-emitting diode (LED) with a device structure of ITO / perovskite / TPBi (45nm) / LiF (1.2nm) / Al (100nm), and the photoelectric properties of the device were tested in a nitrogen glove box. The effective area of the conventional device prepared is 3mm 2 , the effective area of the large area device is 70mm 2 .
[0126] like Figure 2c and Figure 2d As shown, they are SnF 2 In situ absorption and in situ fluorescence (PL) spectra of single-additive tin-based perovskite luminescent heterogeneous bilayer films during spin coating. Figure 2c and Figure 2d It can be seen that the film of this embodiment begins to nucleate around 18 seconds after spin coating, which is about 3 seconds later than the nucleation time of the film without additive in Comparative Example 1, indicating that the SnF additive 2 There is a certain interaction between the two-dimensional perovskite components. In addition, during the spin coating process, the PL peak of the film gradually red-shifted from the initial 810nm to around 880nm, corresponding to the slow growth process of the three-dimensional tin-based perovskite. During this process, no spectral signal of the two-dimensional perovskite appeared, indicating that the crystallization of the two-dimensional perovskite was inhibited by the additive SnF. 2 Suppressed.
[0127] As shown in Figures 3d, 3e, and 3f, the in-situ absorption and in-situ fluorescence spectra of the film of this embodiment during annealing and front and back excitation are shown respectively. As can be seen from Figures 3d, 3e, and 3f, the PL peak position of the film is red-shifted by about 10nm, indicating that the three-dimensional perovskite has further grown.
[0128] like Figure 4b-1 , 4b-2, and 4b-3 are surface and cross-sectional SEM images of the film of this embodiment, respectively ( Figure 4b-1 , 4b-2 is the surface; Figure 4b -3 is the cross section), Figure 4b-1 4b-2 and 4b-3, it can be seen that the surface of the film is similar to the film without additives in Comparative Example 1, and there is also an exposed substrate, and the coverage is not good enough. However, the cross-sectional SEM ( Figure 4b -3) shows that the film is a double-layer heterojunction structure. During the spin coating process, due to the rapid evaporation of the solvent, the perovskite tends to crystallize from the gas-liquid interface. Combined with the in-situ spectral data, it is speculated that the upper layer of the double-layer structure is a three-dimensional perovskite, and the lower layer is a low-dimensional perovskite without fluorescence emission formed by the participation of PEAI, namely PEAI (2-phenylethylamine hydroiodide), HC (NH2 ) 2 I (formamidine hydroiodide), CsI, SnI 2 The precursor components spontaneously formed a perovskite heterogeneous bilayer film through a top-down growth method.
[0129] As shown in FIG5a , the PLQE (photoluminescence quantum efficiency) data of the film of this embodiment that depends on the excitation light intensity is included. As shown in FIG5a , the PLQE of the film of this embodiment is greatly improved compared with the additive-free film of comparative example 1, indicating that the double-layer heterojunction structure helps to improve the quality of the film.
[0130] As shown in Figures 5b and 5c, the JVR (current density-voltage-irradiance) curve and EQE (external quantum efficiency) curve of the LED device prepared using the film of this embodiment are included respectively. It can be seen that the irradiance and EQE of the device of this embodiment are greatly improved compared with the additive-free device of Comparative Example 1, further proving the importance of the double-layer heterojunction perovskite film.
[0131] Example 2
[0132] This embodiment provides a perovskite-perovskite heterogeneous double-layer film, and the difference between this embodiment and embodiment 1 is only that: this embodiment further adds Trp (tryptophan);
[0133] PEAI (2-phenylethylamine hydroiodide), HC (NH 2 ) 2 I (formamidine hydroiodide), CsI, SnI 2 、SnF 2 , Trp (tryptophan) in a molar ratio of 0.3:0.9:0.1:1:0.2:0.08;
[0134] Get the number SnF 2 +Trp dual-additive tin-based perovskite luminescent heterogeneous bilayer films.
[0135] This embodiment also provides a photoelectric device, using the SnF 2 +Trp dual additive tin-based perovskite luminescent heterogeneous double-layer film is used as the active layer of the optoelectronic device; the preparation method of the optoelectronic device is the same as that of Example 1.
[0136] like Figure 2g and Figure 2hAs shown in the figure, the in-situ absorption spectrum and in-situ fluorescence (PL) spectrum of the film of this embodiment during the spin coating process are respectively shown. It can be seen that the crystallization characteristics of the film of this embodiment during the spin coating process are similar to those of the film of Example 1, that is, only the crystallization and growth of three-dimensional perovskite are observed, and the formation of two-dimensional perovskite is not observed. In addition, compared with the SnF 2 Single Additive Thin Film, SnF 2 The PL intensity of the SnF +Trp dual additive film remains basically unchanged during the perovskite nucleation and growth process, indicating that 2 The simultaneous presence of Trp can minimize the impact of defect-assisted non-radiative recombination.
[0137] As shown in Figures 3j, 3k, and 3l, the in-situ absorption and in-situ fluorescence spectra of the film of this embodiment during the annealing process are shown, respectively. It can be seen that the three-dimensional perovskite is mainly distributed on the surface of the film of this embodiment. As the annealing proceeds, a small amount of two-dimensional tin iodide perovskite with n=1 and n=2 is generated at the bottom of the film.
[0138] like Figure 4d-1 , 4d-2, 4d-3 and Figure 6 The following are the surface SEM images of the film of this embodiment and the cross-sectional SEM images of the corresponding LED device ( Figure 4d-1 , 4d-2, 4d-3 are surfaces, Figure 6 As shown in Figure 2, the SnF 2 +Trp dual additive film takes into account SnF 2 The morphological characteristics of the comparative example 2 when the Trp single additive exists are that it has both a higher surface coverage and a double-layer heterojunction structure.
[0139] As shown in Figure 7a, it is a scanning transmission electron microscope (STEM) photo of the cross section of the LED device prepared by the film of this embodiment; as shown in Figure 7b, it is a high angle annular dark field imaging (HAADF) and X-ray energy spectrum element distribution (EDS mapping) of the cross section of the LED device prepared by the film of this embodiment. As can be seen from Figures 7a and 7b, based on SnF 2 +Trp double additives prepared tin-based perovskite film, has a clear double-layer heterojunction structure, Figure 6 In addition, it can be clearly seen that the lower layer of the heterojunction is rich in carbon, while tin and iodine are less, indicating that the two-dimensional perovskite is mainly in the lower layer, which is consistent with the PL spectrum data.
[0140] As shown in FIG. 7c, it is a GIWAXS (grazing incidence wide angle scattering) two-dimensional image of the film of this embodiment (the X-ray incident angle α is 0.3°); as shown in FIG. 7d, it is q of the film of this embodiment at different incident angles.z Axis GIWAXS intensity curve, where the X-ray incident angle α is 0.1° and 0.3°, corresponding to the X-ray penetration depth of about 3-5nm and more than 100nm respectively; as shown in FIG7e, it is a schematic diagram of the out-of-plane structure of the film of this embodiment; as shown in FIG7f, it is a schematic diagram of the in-plane structure of the film of this embodiment; Figure 8 As shown, it is a GIWAXS data analysis diagram of the film of this embodiment. As shown in Figures 7c, 7d, 7e, 7f and 8, the crystal orientations of the upper three-dimensional perovskite and the lower two-dimensional perovskite are perpendicular to the substrate and parallel to the substrate, respectively. Since the sizes of the tin iodine octahedra in the upper and lower layers of perovskite are basically the same, it can be considered that the lattices of the three-dimensional and two-dimensional perovskites are highly matched out of the plane (see Figure 7e for a schematic diagram).
[0141] As shown in Figure 7g, it is a surface transmission electron microscope (STEM) photo of the film of this embodiment; as shown in Figures 7h and 7i, it is a selected area electron diffraction (SAED) photo of the random grains of the film of this embodiment. As shown in Figures 7g, 7h, and 7i, the electron diffraction spots of each grain are composed of three-dimensional and two-dimensional perovskites, and some spots are highly overlapped, indicating that the lattices of the upper three-dimensional perovskite and the lower two-dimensional perovskite are also highly matched in the plane (see Figure 7f for a schematic diagram). Combining the GIWAXS and SAED data, the inventors believe that the SnF-based 2 +Trp dual additives of tin-based perovskite heterogeneous bilayer films have the characteristics of van der Waals epitaxy.
[0142] like Figure 9a As shown, PEAI, HC (NH 2 ) 2 Chemical structure diagram of I(FAI) and Trp, such as Figure 9b-9d As shown in the figure, the liquid NMR spectra of the chemical components of the film prepared in this embodiment are shown. It can be seen that when SnF 2 Under the presence of SnF, the activity of hydrogen protons in FAI and PEAI increases (Figure 9b), resulting in a decrease in their protonation degree, which inhibits the crystallization of three-dimensional and two-dimensional perovskites. In addition, due to the small amount of PEAI used, a small amount of two-dimensional perovskite is oxidized by SnF during the spin coating process. 2 Complete inhibition, which is also SnF 2 A single additive can be the main reason for the formation of a 3D / low-dimensional bilayer perovskite heterojunction. On the other hand, the nuclear magnetic tin spectrum (Figure 9c) shows that SnF 2 There are opposite interactions between SnF and PEAI and Trp. 2 -Trp has a greater interaction than SnF 2-PEAI, which may be the main reason why Trp promotes the n=1 and n=2 2D perovskite forms during annealing. Finally, H NMR spectrum (Figure 9d) shows that Trp additives and SnI 2 There is also interaction between FAI and PEAI, which is the SnF 2 The main reason why Trp can further reduce film defects and improve crystal quality under the presence of Trp is that 2 A comparative schematic diagram of the crystallization process of the +Trp dual additive film is drawn, such as Fig.10 shown.
[0143] As shown in FIG. 11a, the PLQE data of the film of this embodiment is dependent on the excitation light intensity. By comparing FIG. 11a with FIG. 5a, it can be seen that the SnF 2 The PLQE of the +Trp dual additive film is much higher than that of the additive-free film of Comparative Example 1 and the single additive film of Example 1. In particular, the high PLQE (greater than 35%) at low excitation intensity indicates that the film of this example has a lower defect state density.
[0144] As shown in Figures 11b, 11c, 11d, 11e, and 11f, the energy level structure diagram, electroluminescence (EL) spectrum, JVR curve, EQE curve, and peak EQE statistical diagram of the LED device prepared by the film of this embodiment show that although the LED device prepared by the film of this embodiment does not have a hole transport layer, the two-dimensional perovskite in the two-dimensional / three-dimensional tin-based perovskite double-layer heterojunction is conducive to the injection of holes and the blocking of electrons, so it will not affect the injection and recombination of carriers. In addition, the EL spectrum of the device is stable, the leakage current is small, and the irradiance is high (89Wsr -1 m -2 ), high EQE (11.6%), and good device repeatability.
[0145] As shown in Figures 12a, 12b, 12c, and 12d, a large-area LED (effective area 70 mm2) prepared by the film of this embodiment 2 ) device, JVR curve, EQE curve and peak EQE statistical diagram, it can be seen that the preparation method of the film of this embodiment is also applicable to the production of large-area optoelectronic devices with good repeatability, reflecting the superiority of the perovskite heterogeneous double-layer film of the present invention in high-performance optoelectronic devices.
[0146] Example 3
[0147] This embodiment provides a perovskite-perovskite heterogeneous double-layer film, and the difference between this embodiment and embodiment 1 is only that: this embodiment further adds Gly (glycine);
[0148] PEAI (2-phenylethylamine hydroiodide), HC (NH 2 ) 2 I (formamidine hydroiodide), CsI, SnI 2 、SnF 2 , the molar ratio of Gly (glycine) is 0.3:0.9:0.1:1:0.2:0.08;
[0149] Get the number SnF 2 +Gly dual-additive tin-based perovskite luminescent heterogeneous bilayer films.
[0150] This embodiment also provides a photoelectric device, using the SnF 2 +Gly dual additive tin-based perovskite luminescent heterogeneous double-layer film is used as the active layer of the optoelectronic device; the preparation method of the optoelectronic device is the same as that of Example 1.
[0151] like Figure 13a-1 13b-1 are the surface and cross-sectional SEM images of the film of this embodiment. It can be seen that the film of this embodiment and the SnF film of Example 2 are 2 +Trp film, with high coverage and double-layer heterojunction structure, indicating that the use of SnF 2 and amino acid additives are a universal approach to achieve perovskite heterogeneous bilayer films.
[0152] As shown in Figures 13c, 13d, and 13e, they are the X-ray diffraction (XRD) and fluorescence spectra of the film of this embodiment under positive and negative excitation, respectively. It can be seen that the data of Figures 13c, 13d, and 13e further verify the formation of the perovskite heterogeneous double-layer film.
[0153] As shown in Figures 13f, 13g, and 13h, they are the electroluminescence (EL) spectrum, JVR curve, and EQE curve of the LED device prepared by the thin film of this embodiment, respectively. It can be seen that the LED device prepared by the thin film of this embodiment also has high device performance.
[0154] Example 4
[0155] This embodiment provides a perovskite-perovskite heterogeneous double-layer film, and the difference between this embodiment and embodiment 1 is only that: this embodiment further adds 5AVA (5-aminovaleric acid);
[0156] PEAI (2-phenylethylamine hydroiodide), HC (NH 2 ) 2 I (formamidine hydroiodide), CsI, SnI 2 、SnF 2, the molar ratio of 5AVA is 0.3:0.9:0.1:1:0.2:0.08;
[0157] The only polar solvent was DMSO;
[0158] Get the number SnF 2 +5AVA dual-additive tin-based perovskite luminescent heterogeneous bilayer films.
[0159] This embodiment also provides a photoelectric device, using the SnF 2 The double-additive tin-based perovskite luminescent heterogeneous double-layer film with +5AVA is used as the active layer of the optoelectronic device; the preparation method of the optoelectronic device is the same as that in Example 1.
[0160] like Fig.13a 13b-2 and 13b-3 are the surface and cross-sectional SEM images of the film of this embodiment. It can be seen that the film of this embodiment is different from the SnF film of Example 2. 2 +Trp film, with high coverage and double-layer heterojunction structure, indicating that the use of SnF 2 and amino acid additives are a universal approach to achieve perovskite heterogeneous bilayer films.
[0161] As shown in Figures 13c, 13d, and 13e, they are the X-ray diffraction (XRD) and fluorescence spectra of the film of this embodiment under positive and negative excitation, respectively. It can be seen that the data of Figures 13c, 13d, and 13e further verify the formation of the perovskite heterogeneous double-layer film.
[0162] As shown in Figures 13f, 13g, and 13h, they are the electroluminescence (EL) spectrum, JVR curve, and EQE curve of the LED device prepared by the thin film of this embodiment, respectively. It can be seen that the LED device prepared by the thin film of this embodiment also has high device performance.
[0163] Example 5
[0164] This embodiment provides a perovskite-perovskite heterogeneous double-layer film. The difference between this embodiment and embodiment 2 is that: a one-step spin coating method assisted by an anti-solvent (chlorobenzene) is used, and the spin coating speed, time, and temperature are the same as those in embodiment 2;
[0165] Get the number SnF 2 +Trp dual-additive tin-based perovskite luminescent heterogeneous bilayer films.
[0166] This embodiment also provides a photoelectric device, using the SnF 2 +Trp dual additive tin-based perovskite luminescent heterogeneous double-layer film is used as the active layer of the optoelectronic device; the preparation method of the optoelectronic device is the same as that of Example 1.
[0167] like Fig.14a As shown, it is the in-situ fluorescence spectrum of the film of this embodiment at different anti-solvent dropping times during the spin coating process; Figure 14b-1 , 14b-2 are surface SEM photos of the films at different anti-solvent addition times in this embodiment; Figure 14c-1 , 14c-2 are cross-sectional SEM photos of the film of this embodiment; Figure 14d-1 14d-2 are the in situ fluorescence (PL) spectra of the front and back surfaces of the film of this embodiment excited; as shown in Figures 14e, 14f, and 14g, they are the electroluminescence (EL) spectrum, JVR curve, and EQE curve of the LED device prepared by the film of this embodiment, respectively. It can be seen that the addition of anti-solvent near the nucleation time point of perovskite (18th second of spin coating) or after nucleation (30th second of spin coating) basically does not affect the formation of the perovskite heterogeneous double-layer film, and high-performance LED devices can also be prepared.
[0168] Example 6
[0169] This embodiment provides a photoelectric device. This embodiment uses the thin film of Embodiment 2 as the active layer of the photoelectric device. The preparation method of the photoelectric device of this embodiment includes:
[0170] The active layer was deposited onto an ITO substrate coated with a poly(9-vinylcarbazole) (PVK) hole transport layer.
[0171] The electron transport layer 1,3,5-tri(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi) and the electrode LiF / Al were deposited by thermal evaporation to obtain a perovskite light-emitting diode (LED) with a device structure of ITO / perovskite / TPBi (45nm) / LiF (1.2nm) / Al (100nm).
[0172] As shown in Figures 15a and 15b, the surface SEM morphology and fluorescence spectrum of the film deposited on the ITO substrate coated with PVK are shown under front and back excitation. It can be seen that the film morphology and PL spectrum characteristics of this embodiment are similar to those of the film on the ITO substrate in Example 2.
[0173] As shown in Figures 15c, 15d, 15e and 15f, the energy level structure, JVR curve, EQE curve and peak EQE statistical diagram of the LED device of this embodiment show that the photoelectric characteristics of the LED device of this embodiment are similar to those of the device without a hole transport layer and also have high efficiency, indicating that the perovskite heterogeneous double-layer film of the present invention is suitable for both devices without a hole transport layer and devices containing a hole transport layer.
[0174] Example 7
[0175] This embodiment provides a perovskite-perovskite heterogeneous double-layer film. The difference between this embodiment and embodiment 2 is that: the solution is prepared with a mass fraction of 35%; one-step spin coating method (5000rpm, 60s, ambient temperature is 28-32°C);
[0176] This embodiment also provides a solar cell, using the above-mentioned thin film as the active layer of the solar cell; the preparation method of the solar cell includes:
[0177] The active layer was deposited on an ITO substrate coated with a polyethylene dioxythiophene-polystyrene sulfonate (PEDOT:PSS) hole transport layer, or the active layer was directly deposited on an ITO substrate and annealed at 70°C for 10 min;
[0178] A [6,6]-phenyl C71 butyric acid methyl ester (PCBM) electron transport layer is spin-coated on the surface of the active layer;
[0179] The buffer layer LiF and Al electrode were deposited by thermal evaporation to obtain a tin-based perovskite solar cell with a device structure of ITO / perovskite (200nm) / PCBM / LiF / Al or ITO / PEDOT:PSS / perovskite (200nm) / PCBM / LiF / Al, and the photovoltaic properties of the cell were tested in a nitrogen glove box.
[0180] like Fig.16 As shown in a, it is a surface SEM photo of the film of this embodiment; Fig.16 As shown in b, it is the photovoltaic characteristic curve of the solar cell of this embodiment. It can be seen that the film of this embodiment is equally applicable to photovoltaic devices with or without a hole transport layer.
[0181] Example 8
[0182] This embodiment provides a perovskite-perovskite heterogeneous double-layer film. The difference between this embodiment and embodiment 2 is that: the solution is prepared with a mass fraction of 25%; one-step spin coating method (5000rpm, 60s, ambient temperature is 28-32°C);
[0183] This embodiment also provides a photoelectric detector, and the preparation method of the photoelectric detector includes:
[0184] The prepared solution with a mass fraction of 25% is deposited on the interdigital electrodes prepared by magnetron sputtering or evaporation to obtain a photoconductive photodetector. The interdigital electrodes can be common metals such as Au and Ag, which form symmetrical ohmic contacts with the film to achieve the extraction of photogenerated carriers under bias. The current density-voltage curve of the detector in the bright and dark states of this embodiment is shown in Fig.17 , it can be seen that the film of the present invention has good photoelectric detection performance.
[0185] Example 9
[0186] This embodiment provides a perovskite-perovskite heterogeneous double-layer film. The difference between this embodiment and embodiment 1 is that the film components include PEAI, HC (NH 2 ) 2 I, PbI 2 、SnF 2 ;
[0187] PEAI, HC(NH 2 ) 2 I, PbI 2 、SnF 2 The molar ratio is 0.3:1:1:0.1.
[0188] like Fig.18a and 18b The following are the in-situ fluorescence spectra of the thin films of Comparative Example 3 and this embodiment during the spin coating process. It can be seen that the addition of the additive SnF 2 After that, the low-dimensional phase in the mixed-dimensional lead-based perovskite was significantly suppressed, and only three-dimensional perovskite was obtained during the spin coating process. This phenomenon is consistent with the tin-based perovskite heterogeneous bilayer film, indicating that SnF 2 The additives are also applicable to the preparation of lead-based perovskite double-layer films.
[0189] Example 10
[0190] This embodiment provides a perovskite-perovskite heterogeneous double-layer film. The difference between this embodiment and embodiment 1 is that the film components include PEAI, HC (NH 2 ) 2 I. SnI 2 、PbI 2 、SnF 2 ;
[0191] PEAI, HC(NH 2 ) 2 I. SnI 2 、PbI 2 、SnF 2 The molar ratio is 0.3:1:0.9:0.1:0.2;
[0192] like Fig.19a and 19b As shown in the figure, the in-situ fluorescence spectra of the thin films of Comparative Example 4 and this embodiment during the spin coating process are shown. It can be seen that the addition of the additive SnF 2 After that, the low-dimensional phase in the mixed-dimensional Sn-Pb mixed perovskite was significantly suppressed, and only three-dimensional perovskite was obtained during the spin coating process. This phenomenon is consistent with the tin-based perovskite heterogeneous bilayer film, indicating that SnF 2The additives are also suitable for the preparation of tin-lead mixed perovskite double-layer films.
[0193] Comparative Example 1
[0194] This comparative example provides a perovskite film, and the difference between this comparative example 1 and comparative example 1 is only that:
[0195] This comparative example does not add SnF 2 , a mixed-dimensional tin-based perovskite light-emitting film numbered as w / o additive was obtained.
[0196] This comparative example also provides a photoelectric device, using the above-mentioned mixed-dimensional tin-based perovskite light-emitting film numbered as no additive (w / o additive) as the active layer of the photoelectric device; the preparation method of the photoelectric device is the same as that of comparative example 1.
[0197] like Figure 2a and Figure 2b As shown in FIG. 1 , the in-situ absorption spectrum and in-situ fluorescence spectrum of the thin film of this comparative example during the spin coating process are shown in FIG. Figure 2a and Figure 2b It can be seen that the film begins to nucleate around the 15th second of spin coating, and first forms a two-dimensional perovskite with a large n value (large-n, PL peak position 820nm) during the spin coating process (n is the number of tin halide octahedron layers in the two-dimensional perovskite), and then the PL peak gradually blue-shifts, and forms two-dimensional perovskites with n=2 (PL peak position 690nm) and n=1 (PL peak position 620nm) in turn, and finally obtains a mixed-dimensional tin-based perovskite film with different n value distributions. Figure 2b It can also be seen that the crystallization time windows of two-dimensional perovskites with different n values have a certain overlap, indicating that two-dimensional perovskites with different n values in the film are in a state of cross-mixing in space.
[0198] As shown in Figures 3a, 3b, and 3c, the in-situ absorption and in-situ fluorescence spectra of the film of this comparative example during annealing and front and back excitation are shown respectively. As can be seen from Figures 3a, 3b, and 3c, the absorption spectrum of the film does not change much, indicating that the film has been basically crystallized before annealing. In the fluorescence spectrum, the PL peak of the large-n two-dimensional perovskite is blue-shifted by about 20nm, accompanied by a slight enhancement of the PL of the n=1 and n=2 two-dimensional perovskites, indicating that during the annealing process, there is still a part of the large-n crystal phase that transforms to the small-n crystal phase. In addition, the fluorescence spectra of the front and back excitations show obvious n=1, n=2, and large-n two-dimensional perovskite signals, and the n=1 and n=2 signals are stronger when the back is excited, indicating that the film is a mixture of two-dimensional perovskites with different n values, and has a gradient heterojunction feature in which the n value gradually decreases from the surface to the bottom.
[0199] like Figure 4a-1, 4a-2, 4a-3 are the surface and cross-sectional SEM images of the film of this comparative example, respectively ( Figure 4a-1 , 4a-2 is the surface; Figure 4a -3 is the cross section), Figure 4a-1 , 4a-2, and 4a-3 show that there is an exposed substrate on the surface of the film, and the coverage is not good enough, which is not conducive to the construction of high-performance optoelectronic devices. In addition, the film is a single-layer perovskite structure, which is consistent with its mixed dimensional gradient heterojunction characteristics.
[0200] As shown in FIG5a , the PLQE (photoluminescence quantum efficiency) data of the film of this comparative example that depends on the excitation light intensity is included. As can be seen from FIG5a , the PLQE of the film of this comparative example is extremely low, indicating that the defect state density of the film is very high, which is not conducive to the construction of high-performance optoelectronic devices.
[0201] As shown in Figures 5b and 5c, the JVR curve and EQE curve of the LED device of this comparative example are included respectively. It can be seen that the leakage current of the device of this comparative example is very large and the EQE is extremely low, which may be caused by reasons such as low film surface coverage and low PLQE.
[0202] Comparative Example 2
[0203] This comparative example provides a perovskite-perovskite heterogeneous double-layer film. The difference between this comparative example and Example 1 is that SnF 2 Replaced with Trp (tryptophan);
[0204] PEAI (2-phenylethylamine hydroiodide), HC (NH 2 ) 2 I (formamidine hydroiodide), CsI, SnI 2 The molar ratio of Trp is 0.3:0.9:0.1:1:0.08;
[0205] A single-additive tin-based perovskite luminescent heterogeneous double-layer film numbered Trp was obtained.
[0206] This comparative example also provides a photoelectric device, using the above-mentioned single-additive tin-based perovskite luminescent heterogeneous double-layer film numbered Trp as the active layer of the photoelectric device; the preparation method of the photoelectric device is the same as that of Example 1.
[0207] like Figure 2e and Figure 2f As shown, there are the in situ absorption spectrum and in situ fluorescence (PL) spectrum of the thin film of this comparative example during the spin coating process, respectively. It can be seen that the crystallization characteristics of the thin film of this comparative example during the spin coating process are similar to those of the additive-free film of comparative example 1, that is, the two-dimensional perovskite with a large n value crystallizes first, and then the two-dimensional perovskite with a small n value is formed, thus obtaining a thin film in which two-dimensional perovskites with different n values are mixed with each other.
[0208] As shown in Figures 3g, 3h, and 3i, they are the in-situ absorption and in-situ fluorescence spectra of the film of this comparative example during the annealing process and the front and back side excitations, respectively. It can be seen that the crystallization characteristics of the film of this comparative example during the annealing process are similar to those of the additive-free film of comparative example 1, and finally a film with gradient heterojunction characteristics is obtained.
[0209] like Figure 4c-1 , 4c-2, and 4c-3 are surface and cross-sectional SEM images of the film of this comparative example, respectively ( Figure 4c-1 , 4c-2 is the surface; Figure 4c -3 is the cross section), Figure 4c-1 As can be seen from Figures 4c-2 and 4c-3, the cross section of the film is similar to the film without additives in Comparative Example 1, and is also a single-layer structure, indicating that the Trp additive does not have the function of forming a double-layer perovskite heterojunction. However, compared with the film without additives in Comparative Example 1, the film has a higher surface coverage, indicating that there is a certain interaction between the Trp additive and the perovskite precursor, which helps to reduce the holes in the film.
[0210] As shown in FIG. 5a, the PLQE (photoluminescence quantum efficiency) data of the film of this comparative example, which is dependent on the excitation light intensity, is shown in FIG. 5a. As can be seen from FIG. 5a, the PLQE of the film of this comparative example is higher than that of the film of comparative example 1, but much lower than that of the film of example 1, indicating that the Trp single additive has a certain effect in reducing film defects, but there is no SnF 2 The effect of a single additive is significant.
[0211] As shown in Figures 5b and 5c, the JVR (current density-voltage-irradiance) curve and the EQE (external quantum efficiency) curve of the LED device of this comparative example are included respectively. It can be seen that the leakage current of the device of this comparative example is lower than that of the device without additives in comparative example 1 and the device of SnF in Example 1. 2 The EQE of the single additive device is lower than that of the SnF device in Example 1, Comparative Example 1, and Comparative Example 2. However, the EQE of the Trp single additive device in this comparative example is only slightly higher than that of the additive-free device in Comparative Example 1, and is much lower than that of the SnF device in Example 1. 2 The device efficiency of the single additive is consistent with the PLQE data of the thin films obtained under the three conditions of Example 1, Comparative Example 1, and Comparative Example 2, indicating that SnF 2 The double-layer perovskite heterojunction structure under single additive conditions has a more significant effect on improving device efficiency than Trp single additive.
[0212] Comparative Example 3
[0213] This comparative example provides a perovskite-perovskite heterogeneous double-layer film. The difference between this comparative example and Example 9 is that:
[0214] PEAI, HC(NH 2 ) 2 I, PbI 2 、SnF 2 The molar ratio is 0.3:1:1:0.
[0215] Comparative Example 4
[0216] This comparative example provides a perovskite-perovskite heterogeneous double-layer film. The difference between this comparative example and Example 10 is that:
[0217] PEAI, HC(NH 2 ) 2 I. SnI 2 、PbI 2 、SnF 2 The molar ratio is 0.3:1:0.9:0.1:0.
[0218] Comparative Example 5
[0219] This comparative example provides a perovskite-perovskite heterogeneous double-layer film. The difference between this comparative example and Example 2 is that the ambient temperature of the one-step spin coating method is 50°C.
[0220] As shown in Figures 20a and 20b, they are respectively the JVR curve and the EQE curve of the LED device prepared by the thin film of this comparative example. It can be seen that the photoelectric device prepared by the thin film under the condition of too high ambient temperature has poor performance.
[0221] Comparative Example 6
[0222] This comparative example provides a perovskite-perovskite heterogeneous double-layer film. The difference between this comparative example and Example 2 is that the spin coating speed of the one-step spin coating method is 1800 rpm.
[0223] As shown in Figures 21a and 21b, they are respectively the JVR curve and the EQE curve of the LED device prepared by the thin film of this comparative example. It can be seen that the photoelectric device prepared by the thin film under the condition of too low spin coating speed has poor performance.
[0224] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.
Claims
1. A perovskite-perovskite heterogeneous double-layer film, characterized in that: The heterogeneous double-layer film is obtained by a one-step solution method after LX, AX, BX2 and functional additives are dissolved in a polar solvent, and there is a heterojunction interface between the upper and lower layers of the heterogeneous double-layer film; one layer of the heterogeneous double-layer film is an ABX3-type three-dimensional perovskite layer, and the other layer is a low-dimensional perovskite layer; A is CH3NH3 + 、HC(NH2)2 + 、C(NH2)3 + , Cs + , Rb + and K + At least one of; The B is Sn 2+ and / or Pb 2+ ; X is F - , Cl - Br - and I - At least one of .
2. The perovskite-perovskite heterogeneous double-layer film according to claim 1, wherein: The upper and lower layers of the heterogeneous double-layer film, which are composed of the ABX3 three-dimensional perovskite layer and the low-dimensional perovskite layer, also have the structural characteristics of an epitaxial heterojunction.
3. The perovskite-perovskite heterogeneous double-layer film according to claim 1, wherein: The low-dimensional perovskite is at least one of a zero-dimensional perovskite formed by LX and BX2, a one-dimensional perovskite formed by LX and BX2, a two-dimensional perovskite formed by LX and BX2, and a quasi-two-dimensional perovskite formed by LX, AX, and BX2.
4. The perovskite-perovskite heterogeneous double-layer film according to claim 1, wherein: The molar ratio of LX, AX, BX2 and functional additives is (0.05-1): (0.8-1.5): 1: (0.01-0.8); The total mass concentration of LX, AX, BX2 and functional additives in the solution formed by LX, AX, BX2, functional additives and polar solvent is 5-50wt%; The LX is an organic ammonium salt and / or an organic phosphine salt obtained by an acid-base reaction between an organic amine and / or an organic phosphine and a hydrohalic acid; preferably, the organic amine is an organic amine having a carbon number of not less than 3; preferably, the organic phosphine is an organic phosphine having a carbon number of not less than 3; preferably, the hydrohalic acid is at least one of hydrofluoric acid, hydrochloric acid, hydrobromic acid and hydroiodic acid.
5. The perovskite-perovskite heterogeneous double-layer film according to claim 1, wherein: The polar solvent is at least one of formamide, acetamide, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, cyclopentane, tetramethylene sulfoxide, 1,3-dimethylpropylene urea, γ-butyrolactone, γ-valerolactone, N-alkylpyrrolidone, acetonitrile, ethylene carbonate, propylene carbonate, methylammonium formate, methylammonium acetate, butylammonium acetate, methylammonium propionate and methylammonium isobutyrate; preferably, the polar solvent is a mixture of N,N-dimethylformamide and dimethyl sulfoxide; The functional additives include additive M, and optionally additive N.
6. The perovskite-perovskite heterogeneous double-layer film according to claim 5, wherein: The additive M is at least one of SnF2, SnF4, PbF2, ZnF2, MnF2, CuF2, CdF2, FeF2, FeF3, NiF2, AlF3, CaF2, MgF2, SrF2, AgF, tri(4-fluorophenyl)phosphine, tri(4-fluorophenyl)phosphine oxide and crown ether; The additive N is at least one of an amino acid additive, a vitamin additive, a quaternary ammonium salt additive and a quaternary phosphonium salt additive. Preferably, the additive N is at least one of alanine, valine, leucine, isoleucine, methionine, phenylalanine, tryptophan, tyrosine, asparagine, cysteine, glutamine, serine, threonine, aspartic acid, glutamic acid, arginine, histidine, lysine, glycine, 5-aminovaleric acid and proline.
7. The perovskite-perovskite heterogeneous double-layer film according to claim 1, wherein: The one-step solution method comprises coating a solution formed by the LX, AX, BX2, functional additives and polar solvent on a substrate to obtain the heterogeneous double-layer film; The substrate is at least one of an organic small molecule, an organic polymer, paper, leather, a metal, an inorganic compound, glass and a ceramic, preferably indium tin oxide, fluorine-doped tin oxide, lithium fluoride, tin oxide, zinc oxide, nickel oxide, poly(9-vinyl carbazole), polyethylene dioxythiophene-polystyrene sulfonate, poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], poly(N,N'-bis-4-butylphenyl-N,N'-biphenyl)benzidine, N,N' - at least one of diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine, 1,3,5-tri(1-phenyl-1H-benzimidazol-2-yl)benzene, 1,3,5-tri(3-pyridyl-3-phenyl)benzene, 4,6-bis(3,5-di(3-pyridyl)phenyl)-2-methylpyrimidine and poly[(9,9-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine)]; The one-step solution method is at least one of a one-step spin coating method, a one-step blade coating method and a one-step spray coating method; The operating conditions of the one-step spin coating method include: an ambient temperature of 5-45° C., preferably 20-40° C.; and a spin coating rotation speed of 2000-10000 rpm, preferably 5000-10000 rpm.
8. Use of the perovskite-perovskite heterogeneous double-layer film according to any one of claims 1 to 7 in preparing an active layer of a photovoltaic device.
9. The use according to claim 8, wherein: The optoelectronic device includes, in addition to the active layer, a substrate, an anode, an electron transport layer and a cathode, and optionally includes a hole transport layer.
10. The use according to claim 8, wherein: The optoelectronic device is at least one of a solar cell, a light emitting diode, a photodetector and a memristor.